Compensation, Work-Life Balance, and Job Satisfaction Influencing Retention of Generation Z - Fatimah Azzhara Al-Idrus; Heriyadi Heriyadi; Endah Mayasari; Maria Christiana Iman Kalis (Penerbit Goodwood, 2026)
Purpose: The research in this study aims to examine the effects of compensation and work-life balance on employee retention among Generation Z, with job satisfaction as a mediating variable. Methodology: The research employed a quantitative design by distributing structured questionnaires to Generation Z employees working in Indonesia’s private trade sector. A total of 200 valid responses were collected through random sampling. Data were analysed using Structural Equation Modeling (SEM) with the support of SmartPLS version 4 to assess both the measurement and structural models. Results: The findings reveal that Generation Z employees in Indonesia consider compensation and a dynamic work-life balance to be crucial factors in shaping job satisfaction and retention. This suggests that organizations should balance financial rewards with supportive work-life policies to retain young talent effectively. Conclusion: The conclusion this study delivers shows that compensation supports job satisfaction but does not necessarily ensure employee retention, whereas work-life balance has a stronger influence on Generation Z’s commitment. Integrating both provides guidance for HRM and supports the Indonesia Emas 2045 vision. Contribution: This study contributes to the literature on human resource management and generational workforce behavior, while providing practical strategies for retaining Generation Z employees in support of Indonesia Emas 2045. Limitation: This study is limited by its sample size of 200 respondents from the private trade sector, which may not fully represent the broader population of Generation Z employees in Indonesia.